The status of local purchasing order in a contract of sale of goods: a critique of the rights-based approach in Abba v. Shell petroleum development company of Nigeria limited (2022)
This paper examined the judgment of the Supreme Court of Nigeria in Abba v. Shell Petroleum Development Company of Nigeria Limited on the status of Local Purchase Order (LPO) in a contract of sale of goods. Contrary to the general rule in most countries of the world, including the United States of America and Uganda, that the LPO constitutes an offer in the law of contract, the Supreme Court held that it was an invitation to treat which is not enforceable in law. Consequently, this paper subjects this decision into a critical examination with a view to determining its accuracy. For this purpose, it interrogates the role of offer and acceptance and in particular the invitation to treat in the formation of the contract of sale of goods. It also discusses the question of what time it could be said that parties have entered into a contract of sale of goods. It interrogates the legal Status of the LPO in commercial transactions and how the status might affect the result of the application of offer and acceptance in a contract, particularly the contract of sale of goods. It concludes that, although the decision in Abba's case cannot be reconciled with similar decisions not only in Nigeria but also globally, it can be justified using the rights-based approach.